Anomalous brachiocephalic trunk crossing the trachea: a rare vascular challenge in tracheostomy-case report and surgical considerations - George, Jomy; James, Lijo; Puneeth, K C; Mohan, Aiswarya (Indian Journal of Case Reports, 2025)
A 66-year-old woman with a history of breast cancer diagnosed 2 years ago, hypertension, and hypothyroidism developed progressive quadriparesis and autonomic dysfunction, diagnosed as Guillain-Barré syndrome. She required mechanical ventilation due to severe respiratory distress. Tracheostomy was planned for prolonged ventilator support; however, abnormal neck pulsations at the surgical site raised concern for a vascular anomaly. Doppler ultrasonography and computed tomography angiography revealed a high-riding aberrant brachiocephalic trunk (BCT) traversing anterior to the trachea, altering the standard surgical approach. BCT anomalies, though rare, can pose life-threatening risks during neck surgeries. This case underscores the importance of pre-operative imaging when vascular anomalies are suspected. Recognizing such variations is crucial for surgical planning, enhancing patient safety, and guiding modified procedures to reduce complications.